Methods of assessing the competitiveness of the company staff - Iryna Shvets; Hanna Marykon (Cхід, 2013)
In this article authors are develop the complex method of estimation of competitiveness of personnel by the use of ball estimation of its basic components. To the indexes which are estimated belong: job performances, labor productivity, labor discipline, personal, professional and professional qualities, health and professional mobility. The results of estimation allow to define the level of competence depending on a presence and degree of display for the worker of the set descriptions